THE FUTURE OF ARTIFICIAL INTELLIGENCE AND ITS IMPACT ON EMPLOYMENT. - Ibrohimova Mohinur Vohid qizi; Ilxomova Husnida Ilyos qizi (TADQIQOTLAR, 2025)
Abstract. Artificial intelligence (AI) is rapidly advancing, with the potential to transform industries and society as a whole. This thesis explores the future of AI and its impact on employment. By reviewing current trends and examining projections for AI’s role in various sectors, the study assesses both the opportunities and challenges AI poses to the workforce. While AI can improve productivity and create new job categories, it also raises concerns about job displacement and skill gaps. The research provides recommendations for mitigating negative effects and ensuring a fair transition for workers affected by AI advancements.